Social media as public opinion: How journalists use social media to represent public opinion. (August 2019) - McGregor, Shannon C
Public opinion, as necessary a concept it is to the underpinnings of democracy, is a socially constructed representation of the public that is forged by the methods and data from which it is derived, as well as how it is understood by those tasked with evaluating and utilizing it. I examine how social media manifests as public opinion in the news and how these practices shape journalistic routines. I draw from a content analysis of news stories about the 2016 US election, as well as interviews with journalists, to shed light on evolving practices that inform the use of social media to represent public opinion. I find that despite social media users not reflecting the electorate, the press reported online sentiments and trends as a form of public opinion that services the horserace narrative and complements survey polling and vox populi quotes. These practices are woven into professional routines – journalists looked to social media to reflect public opinion, especially in the wake of media events like debates. Journalists worried about an overreliance on social media to inform coverage, especially Dataminr alerts and journalists' own highly curated Twitter feeds. Hybrid flows of information between journalists, campaigns, and social media companies inform conceptions of public opinion.